Mechanisms of metal nanoparticles nucleation and growth studied by radiolysis. (April 2020) - Belloni, J.; Marignier, J.-L.; Mostafavi, M.
Abstract: The ultradivided matter is used for long in various applications, for example in colloids, inks and paints, cosmetics, stained glasses, catalysts, photographic emulsions, ... But the progressive need of nanoparticles for various miniaturized devices and the different approaches for the synthesis have suddenly increased. All of the bottom-up synthesis methods from a diluted precursor to metal nanoparticles imply several steps: a reduction reaction of ionic precursors by electron transfer, inducing the nucleation of atoms then the growth of the seeds into particles, more or less inhibited by stabilizers. The final size, shape, structure and dispersity of the particles strongly depend on the thermodynamics and the kinetics of these steps. The interaction of high energy radiation with the solvent provides, quantitatively and homogeneously distributed in the bulk, strong electron donors (solvated electrons, reducing radicals) which reduce metal ions as precursors into atoms. The radiation chemistry, on one hand in the steady state regime with an accurate knowledge of the yields of all the radiolytic products, and on the other hand in the pulse regime giving access to time-resolved data, constitutes a unique tool to elucidate the detailed mechanisms and to provide the keys of really controlling these processes in view of various applications.